Understanding electric vehicle drivers' parking and charging choice behaviour - Huang, Guohua (Nanyang Technological University, 2022)
As Singapore adopts the Electric Vehicles (EVs) and phases out convention vehicles running on Internal Combustion Engine (ICE), the government has sought to deploy 60,000 electric vehicle chargers in Singapore as part of the Singapore Green Plan 2030. One major hurdle to EV adoption is charging – both the charging time and availability of charging infrastructure. As the world phases out ICE Vehicles, more understanding of EV parking and charging is required to manage the worldwide demand and supply of charging infrastructure.